Riots, social movements and the “making of the working class”: forms of popular organization and urban protest in São Paulo (1945-1964) | Quebra-quebras, movimentos sociais e a “formação da classe trabalhadora”: formas de organização popular e protesto urbano em São Paulo (1945-1964) - Silva, Marcos Virgílio da (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
The present article investigates the expressions of popular demands and discontent within three forms of manifestation: riots, non-class-based “social movements”, and movements organized by the “working classes” or “workers”. By examining these different movements we expect to problematize the recurring literature surrounding these movements, which has often characterized them as being insufficient or incomplete, reactive and subordinate to higher authorities, thus being void of any transforming power. It is therefore hoped that this article may contribute to a debate that would seek to transcend the very frequently encountered viewpoint that popular protests have been sporadic, rare phenomena throughout Brazilian history.